Development of Creative Thinking Evaluation Tool Utilizing Microsoft Sway Application in the Context of Pythagorean Theorem Material - Siswanto, Deny Hadi; Alghiffari, Eka Kevin; Andriyani, Andriyani (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
The aim of this research is to develop an evaluation tool utilizing the Microsoft Sway application to assess the creative thinking abilities of eighth-grade students in comprehending the Pythagorean Theorem material. This study is a development research with a development model that includes measuring instrument specifications, statement or question writing, statement or question review, instrument compilation, trial, instrument selection and assembly, instrument administration, and scale and norm writing. The data analysis method used involves expert validation and student responses through questionnaires. The validity results indicate that all test items have been categorized as valid. The evaluation tool's reliability level reached 0.611, indicating a sufficient level of reliability. The average difficulty level of the questions is 0.66, classified as moderate, while the average discrimination power is 0.35, indicating a sufficient discrimination power. The results of this research, which have been validated by media experts with a final percentage of 84.82%, are classified as highly suitable. Content experts provided a final percentage of 79.00%, indicating feasibility. Student responses to this evaluation tool reached a final percentage of 93.17%, indicating a very high level of interest. Thus, it can be concluded that the development of a creative thinking evaluation tool based on the Microsoft Sway application for the Pythagorean Theorem material is suitable for use as an evaluation instrument in mathematics learning.